THE MANAGEMENT OF INDONESIAN DOMESTIC WORKERS BASED ON GOVERNMENT PARTICIPATION IN CHINA - Elisabeth Tanti Pudiastuti; Sukmo Hadi Nugroho (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Indonesian domestic workers have been an interesting issue for several years. The existence of the workers, in one side, has played significant roles in generating income, reducing poverty, and generating economic development of the sending country. But in another side, they have also created complicated problems. The problems have frequently involved multiple stakeholders including governmental, non-governmental institution, and private sectors. Therefore, this study focuses on explaining Government participation in managing Indonesian domestic workers in China. China was chosen due to the number of the domestic workers. In order to explain the phenomenon, the researchers used qualitative research method. Consequently, the primary data was collected from interview. In addition, documentary analysis was also used in order to support the data. The study showed that there are at least some Government involved in managing Indonesian domestic workers such as National Agency of Placement and Protection of Indonesian Workers, Private Agencies in sending and receiving country, Ministry of Labor, and Ministry of Foreign Affairs. There are three processes of worker placement namely pre-placement, while-placement, and post placement. The private agencies participated practically in almost all of the process including recruitment, providing education and training, and placement the workers. While, other Government participate in providing administrative process such as providing agreement, documents needed, legalizing private agencies, and collecting the data of the labors. However, administrative process was not run properly. It was because the workers and private sectors have to report their conducting activities. This condition gave impact to the lack of control to the activities. This was also exacerbated by the lack of participation from the workers. They don’t have any information about the job and power to get protection. It was because of the existence of the law and lack of education. Therefore, knowledge about job, law, and involved Government was needed to increase participation and protection of the worker. Keywords: Domestic Workers, Job Placement, Job Protection, Government Participation